Interrelation Between Fibroblasts and T Cells in Fibrosing Interstitial Lung Diseases - Lai, Yunxin; Wei, Xinru; Ye, Ting; Hang, Lilin; Mou, Ling; Su, Jin (Frontiers in Immunology, 2021)
Interstitial lung diseases (ILDs) are a heterogeneous group of diseases characterized by varying degrees of inflammation and fibrosis of the pulmonary interstitium. The interrelations between multiple immune cells and stromal cells participate in the pathogenesis of ILDs. While fibroblasts contribute to the development of ILDs through secreting extracellular matrix and proinflammatory cytokines upon activation, T cells are major mediators of adaptive immunity, as well as inflammation and autoimmune tissue destruction in the lung of ILDs patients. Fibroblasts play important roles in modulating T cell recruitment, differentiation and function and conversely, T cells can balance fibrotic sequelae with protective immunity in the lung. A more precise understanding of the interrelation between fibroblasts and T cells will enable a better future therapeutic design by targeting this interrelationship. Here we highlight recent work on the interactions between fibroblasts and T cells in ILDs, and consider the implications of these interactions in the future development of therapies for ILDs.